General Strategy to Construct Hierarchical TiO2 Nanorod Arrays coupling with Plasmonic Resonance for Dye-sensitized Solar Cells. (10th August 2015) - Yumin, Liu; Minli, Zhang; Yun, Jiang; Yu, Xia; Weiwei, Sun; Xing-Zhong, Zhao
Graphical abstract: The general strategy reported here will offer a facile approach to improve the electron transfer process via the construction of HTNRs, and to further enhance the light harvesting of dye molecules by introduction of SPR effects. Abstract: We demonstrate a general strategy to construct hierarchical TiO2 nanorod arrays (HTNRs) coupling with plasmon resonant metallic nanoparticles for dye-sensitized solar cells (DSCs). The electron transfer and interfacial recombination process have been optimized via the construction of photoanodes. Moreover, localized electric fields produced by the introduction of Au nanoparticles could excite dye molecules more effectively than the incident far-field light, resulting in further enhancement of light adsorption and photocurrent generation of DSCs. The synergistic effect of surface plasmon resonance (SPR) and constructed HTNRs has been investigated by optical spectroscopy, J - V, IPCE, EIS and OCVD measurements. An evidently improvement in energy conversion efficiency of the devices beyond 25% has been achieved via the cooperation of constructed HTNRs and SPR effects in DSCs.